The Effect of Career Aspiration and Career Calling on Perception of Employability with Opportunity Awareness as an Intervening Variable and Effect of Career Aspiration and Career Calling on Opportunity Awareness and Perceived Employability - Prianka Ratri Nastiti; Noni Setyorini; Rr. Hawik Ervina (PT Mattawang Mediatama Solution, 2023)
Perceived employability, career aspirations, career calling, and opportunity awareness are important things that need to be considered for alumni and final year students in higher education because it is related to the preparation they will face after graduating from college, namely when they enter the world. real work. This study uses a sample of alumni and final year students of public and private universities in the city of Semarang. The sample used is 100 respondents and data processing is done using SMART PLS3. The results show that career aspirations have a positive and significant effect on opportunity awareness, career aspirations have a negative and significant effect on perceived employability, career calling have a positive and significant impact on opportunity awareness, career calling have a negative and significant effect onperceived employability, opportunity awareness has a positive and significant impact on perception employability, while the opportunity awareness variable is able to mediate the effect of career aspirations on perceived employability, and opportunity awareness is able to mediate the effect of career calling on perceived employability.